Coargumenthood and the processing of pronouns. Issue 10 (26th November 2018) - Cunnings, Ian; Sturt, Patrick
ABSTRACT: We report three eye-movement experiments and an offline task investigating structural constraints on pronoun resolution in different contexts. This included "coargument" contexts in which a pronoun was the direct object of a verb ("The surgeon remembered that Jonathan had noticed him"), so-called picture noun phrases ("The surgeon remembered that Jonathan had a picture of him") and picture noun phrases with a possessor ("The surgeon remembered about Jonathan's picture of him"). In each eye-movement experiment, we observed longer reading times when the nonlocal antecedent ("the surgeon") mismatched in stereotypical gender with the pronoun, but little evidence of the gender of the local antecedent ("Jonathan") influencing reading times. The offline task suggested readers occasionally interpret pronouns as referring to local antecedents, especially in non-coargument contexts. These results suggest that structural constraints constitute more highly weighted cues to antecedent retrieval than gender congruency during the initial stages of memory retrieval during pronoun resolution.